A structured training program for minimally invasive esophagectomy for esophageal cancer— a Delphi consensus study in Europe. Issue 3 (7th November 2017) - Visser, E; van Rossum, P S N; van Veer, H; Al-Naimi, K; Chaudry, M A; Cuesta, M A; Gisbertz, S S; Gutschow, C A; Hölscher, A H; Luyer, M D P; Mariette, C; Moorthy, K; et al.
SUMMARY: Evidence suggests that structured training programs for laparoscopic procedures can ensure a safe standard of skill acquisition prior to independent practice. Although minimally invasive esophagectomy (MIO) is technically demanding, no consensus on requirements for training for the MIO procedure exists. The aim of this study is to determine essential steps required for a structured training program in MIO using the Delphi consensus methodology. Eighteen MIO experts from 13 European hospitals were asked to participate in this study. The consensus process consisted of two structured meetings with the expert panel, and two Delphi questionnaire rounds. A list of items required for training MIO were constructed for three key domains of MIO, including (1) requisite criteria for units wishing to be trained and (2) to proctor MIO, and (3) a framework of a MIO training program. Items were rated by the experts on a scale 1–5, where 1 signified 'not important' and 5 represented 'very important.' Consensus for each domain was defined as achieving Cronbach alpha ≥0.70. Items were considered as fundamental when ≥75% of experts rated it important (4) or very important (5). Both Delphi rounds were completed by 16 (89%) of the 18 invited experts, with a median experience of 18 years with minimally invasive surgery. Consensus was achieved for all three key domains. Following two rounds of a 107-item questionnaire, 50 items were rated as essential for training MIO. A consensus among European MIO experts on essential items required for training MIO is presented. The identified items can serve as directive principles and core standards for creating a comprehensive training program for MIO.